Effect of a low gas pressure plasma treatment on copper substrate used for carbon nanotubes synthesis - C. Suttichart (2018)
© 2016 Effects of two different mixtures of working gas, namely, 10%Ar + 90%H2and 10%Ar + 90%N2, used in low pressure plasma treatment of copper substrate surface modification in the synthesis of carbon nanotubes by the ACVD method were investigated and compared. After a chemical vapor deposition process, the samples were characterized by SEM and TEM microscopy and X-ray diffraction technique. Analysis of the micrographs and spectra obtained showed that H2plasma (obtained from a mixture of 10%Ar + 90%H2) treatment developed higher degree of surface roughness, smaller contact angle which leads to better hydrophilic property of the treated surface, and stronger adhesion of the Cu substrate which resulted in higher yields of the synthesized CNTs. In addition, the origins of these results were discussed with respect to the process parameters and hence the plasma environment. Abstract code AP 19